FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI pada tahun 2013-2017) - Putri, Devi Diana; Hasan, Amir; A, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study was aimed to examine the influence auditor reputation, debtdefault, disclosure, company size, and previous year’s audit opinion to theacceptance of going concern opinion.The population of this study are manufaturecompanies listed on the Indonesian Stock Exchange period 2013 – 2017. Thesamples of the study are all companies were selected by purposive samplingmethod. Based on the criteria, 49 companies were chosen as the samples of thisstudy. This study used logistic regression analysis was used to test whether theindependent variables affect the dependent variable. Data analysis for hypothesistest was done with Statistical Package for the Social Sciences (SPSS) ver. 24.Result of this study give evidence that the auditor reputation, debt default,company size and previous year's audit opinion had a significant effect on theaudit going concern opinion on manufacturing companies during the period 2013to 2017. While the disclosure do not significantly effect on the going concernopinion. Value of Negelkerke R Square is 0.795, which means that the variabilityof the dependent variable can be explained by the independent variable as 79,5%,while the remaining variables 20,5% is explained by the variability of othervariables outside the model study.Keywords : Auditor Reputation, Debt Default, Disclosure, Company Size,Previous year’s Opinion, and Going Concern